2009
DOI: 10.1007/s11136-009-9468-0
|View full text |Cite
|
Sign up to set email alerts
|

Are gender-associated differences in quality of life in colorectal cancer patients disease-specific?

Abstract: The vast majority of studies on gender-associated differences in quality of life compare male and female oncological patients and neglect the issue of the disease-specificity of such differences. Our study revealed that women and men suffering from colorectal cancer scored differently across many aspects of quality of life, but with the exception of diarrhea, these differences were also found in the general population, i.e. they indicated no gender-specific reaction to disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 35 publications
4
20
1
Order By: Relevance
“…Shorter time since diagnosis has been associated previously with worse psychological well-being [7] or intrusive thoughts [16], although some longitudinal studies did not confirm this association [17]. With respect to sex and depressive symptoms, the findings have been inconclusive thus far [8,[18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shorter time since diagnosis has been associated previously with worse psychological well-being [7] or intrusive thoughts [16], although some longitudinal studies did not confirm this association [17]. With respect to sex and depressive symptoms, the findings have been inconclusive thus far [8,[18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…The reliability and validity of the BAI are well established. The BAI scale score was categorized into the following severity categories: none (BAI scale score 0-9), mild (10-18), moderate (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29), and severe (30-63) [14].…”
Section: Outcome Measuresmentioning
confidence: 99%
“…A diagnosis of cancer places a heavy toll on the patient, negatively affecting life in physical, psychological, and social domains. [48]…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have identified that gender is a factor that may influence QOL in cancer patients. [3748] Further, there has been research reporting higher levels of psychological distress among female cancer patients. [8] Similar to this study, Pud[37] reported that female patients had significantly lowered psychological QOL than their male counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas CRC prevalence rates in men and women are similar [1], gender and marital status have been shown to affect survival and quality of life, with females and single/ widowed status often associated with poorer outcomes [32][33][34]. Tuinsdra et al [33] have reported that females appear to be more vulnerable to stress than males when facing CRC.…”
Section: Discussionmentioning
confidence: 99%